Organic compounds destruction by a relativistic eleсtron beam in waste-waters - Antipov, V.S.; Babych, E.M.; Berezhna, I.V.; Gorban, N.S.; Grytsenko, A.V.; Kovpik, O.F.; Kornilov, E.O.; Kiselev, V.A.; Linnik, A.F.; Revyakina, N.Yu.; Uskov, V.V. (Вопросы атомной науки и техники, 2004)
The electron beam influence on the decomposition of organic compounds in effluents has been investigated. In the tests, waste-water has been processed with a relativistic electron beam of the energy 3...4 MeV, formed with a linear resonance accelerator. The model samples of the following solutions have been put on trial: nitrite-, nitrate-, ammonium- and phosphate ions, glucose and purified kerosene. The results of the investigations have indicated that the application of relativistic electron beams is prospective for the water purification from these organic compounds. Виконано цикл досліджень по впливу релятивістського електронного пучка на руйнування модельних зразків розчинів нітрит-іонів, нітрат-іонів, амонійного іону, фосфат-іонів, глюкози, гасу. Показано, що використовування релятивістських електронних пучків є перспективним для очистки стічних вод від цих сполук. Выполнен цикл исследований по влиянию релятивистского электронного пучка на разрушение модельных образцов растворов нитрит-ионов, нитрат-ионов, амонийного иона, фосфат-ионов, глюкозы, керосина. Показано, что использование релятивистских электронных пучков является перспективным для очистки сточных вод от этих соединений.